From inside looking in how practicum students experience supervision - Mateo, Niño Jose (Philippine Journal of Counseling Psychology, 2010)
A study was conducted to understand how supervision is being delivered at the sites. Fifteen graduate students taking up Master's and Doctoral practicum were interviewed about their supervision as well as how they describe their supervisors, the sites and the supervision sessions. The respondents defined supervision in terms related to guidance, mentoring and consultation. They reported supervisors who are accommodating and approachable, yet busy and overburdened. They also reported a lack of of appropriate supervision focus and insufficient monitoring from both the academic institution and the site. They reported, however, a general satisfaction with their supervision experience. Results were compared to current ideal standards of supervision. Recommendations were given for the further improvement of the delivery of supervision.